Securities Post-trading Infrastructure – Past, Present and Future - Béres, Dániel (Public Finance Quarterly, 2023)
The two fundamental institution of securities post-trading landscape is the central counterparty (CCP) and the central securities depository (CSD). While the institution of CCP was developed to mitigate risk of the counterparties participating in (securities) trading, the development of CSD was driven by the need of increasing market efficiency by securitization and capital flows. Both institutions was developed by market needs, but later on, following the 2008 financial crisis the importance of these institutions has increased significantly since they have fundamental role in ensuring safe and sound financial markets and crossborder capital flows. All around the world strict regulatory regimes are formulated regarding CCPs and CSDs. As a consequence of 2008 crisis, trade repositories (TR) are established in order to store OTC derivative transaction data. In the future, due to the technological development, the post-trading landscape may change. One direction may be to introduce real spot markets (without settlement cycle) and the other one may be to implement distributed ledger technology to replace the current post-trading framework.